Numerical Simulation of Cumulative Nonlinear Symmetric Lamb Waves in an Aluminium Plate. (2017) - Ong, W.H.; Chiu, W.K.; Rose, L.R.F.
Abstract: Cumulative nonlinear Lamb waves have been widely reported in experimental studies. These studies report on cases where nonlinear Lamb waves will increase in amplitude with propagation distance because the entire specimen is responsible for generating harmonics. The applications for nonlinear Lamb wave propagation include distributed damage such as fatigue and even identifying one type of metallic alloy from another. In this paper, nonlinear elasticity is presented as the key mechanism responsible for cumulative second order Lamb wave generation. This is followed by a series of numerical simulations which will shed light on how to achieve efficient generation of cumulative nonlinear Lamb waves. The effects of excitation amplitude and frequency-thickness will be explored through numerical modelling. The numerical results presented in this paper will support rules prescribed by other authors. It is found that both factors are crucial in producing a measurable nonlinearity.